Angiopoietin-like proteins and postprandial partitioning of fatty acids. Issue 1 (February 2022) - DiDonna, Nicole M.; Chen, Yan Q.; Konrad, Robert J.
Abstract : Purpose of review: Over the last two decades, evolving discoveries around angiopoietin-like (ANGPTL) proteins, particularly ANGPTL3, ANGPTL4, and ANGPTL8, have generated significant interest in understanding their roles in fatty acid (FA) metabolism. Until recently, exactly how this protein family regulates lipoprotein lipase (LPL) in a tissue-specific manner to control FA partitioning has remained elusive. This review summarizes the latest insights into mechanisms by which ANGPTL3/4/8 proteins regulate postprandial FA partitioning. Recent findings: Accumulating evidence suggests that ANGPTL8 is an insulin-responsive protein that regulates ANGPTL3 and ANGPTL4 by forming complexes with them to increase or decrease markedly their respective LPL-inhibitory activities. After feeding, when insulin levels are high, ANGPTL3/8 secreted by hepatocytes acts in an endocrine manner to inhibit LPL in skeletal muscle, whereas ANGPTL4/8 secreted by adipocytes acts locally to preserve adipose tissue LPL activity, thus shifting FA toward the fat for storage. Insulin also decreases hepatic secretion of the endogenous ANGPTL3/8 inhibitor, apolipoprotein A5 (ApoA5), to accentuate ANGPTL3/8-mediated LPL inhibition in skeletal muscle. Summary: The ANGPTL3/4/8 protein family and ApoA5 play critical roles in directing FA toward adipose tissue postprandially. Selective targeting of these proteins holds significant promise for the treatment of dyslipidemias, metabolic syndrome, and their related comorbidities.